Conservative Management of Blunt Pancreatic Trauma in Children: A Single Center Experience - Abbo, Olivier; Lemandat, Aurélie; Reina, Nicolas; Bouali, Ourdia; Ballouhey, Quentin; Carfagna, Luana; Lemasson, Frederique; Harper, Luke; Sauvat, Frederique; Galinier, Philippe (European Journal of Pediatric Surgery, 2013)
Introduction Blunt trauma of the pancreas represents a significant part of abdomen trauma in children with an incidence estimated at around 10%. If the conservative management is widely accepted concerning the stages I and II, it remains controversial concerning stages III and IV. The aim of our study was to perform a descriptive analysis of the nonoperative management, with a focus on the occurrence of pseudocysts.Materials and Methods The charts of the patients treated in our center for pancreatic trauma from 1990 to 2010 have been reviewed. It was defined by an initial lipase greater than three times the norm and an abnormal computed tomography scan.Results A total of 36 patients were included, with 26 boys (72%) and 10 girls (28%) with an average age of 8.7 years. The trauma was isolated in 13 cases (36.1%) and in 23 cases, there were other associated lesions (mainly liver [n = 9] and spleen [n = 5]). Pancreatic injuries were graded as follows: I (n = 21), II (n = 2), III (n = 7), and IV (n = 6). Pseudocysts occurred in 11 patients (30.5%) mainly in grades III (n = 3) and IV (n = 7), with an average delay of 17 days. Initial management of pseudocysts was conservative in six patients (54.6%), whereas five patients required mimi-invasive procedures.Conclusion Nonoperative management remains a safe way to treat pancreatic injuries despite an average 30% rate of pseudocyst (PC) appearance. It allows a reduction in the number of children who required procedures to less than half of the patients where PC occurred. Furthermore, these procedures were exclusively mini-invasive.
Keywords: pancreatic traumatism; conservative management; pseudocyst